2013
DOI: 10.1016/j.neuroscience.2012.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Acute N-methyl-d-aspartate receptor hypofunction induced by MK801 evokes sex-specific changes in behaviors observed in open-field testing in adult male and proestrus female rats

Abstract: Schizophrenia is a complex constellation of positive, negative and cognitive symptoms. Acute administration of the non-competitive antagonist of the N-methyl D-aspartate receptor (NMDAR) dizocilpine (MK801) in rats is one of few preclinical animal models of this disorder that has both face and/or construct validity for these multiple at-risk behavioral domains and predictive power for the efficacy of therapeutic drugs in treating them. This study asked whether and to what extent the rat NMDAR hypofunction mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 75 publications
2
15
1
Order By: Relevance
“…In contrast, male brains are more responsive to the g-aminobutyric acid (GABA) receptor agonist diazepam and the cannabinoid agonist CP55940 in reducing hippocampal and hypothalamic BDNF expression (Kellogg et al, 2000;Lopez-Gallardo et al, 2012). It remains to be explored whether sex-specific BDNF expression is responsible for efficacy of these receptor antagonists/agonists that display obvious sex-specific activities (Tseng and Craft, 2001;Feinstein and Kritzer, 2013).…”
Section: Sex Differences In Circulating Bdnfmentioning
confidence: 99%
“…In contrast, male brains are more responsive to the g-aminobutyric acid (GABA) receptor agonist diazepam and the cannabinoid agonist CP55940 in reducing hippocampal and hypothalamic BDNF expression (Kellogg et al, 2000;Lopez-Gallardo et al, 2012). It remains to be explored whether sex-specific BDNF expression is responsible for efficacy of these receptor antagonists/agonists that display obvious sex-specific activities (Tseng and Craft, 2001;Feinstein and Kritzer, 2013).…”
Section: Sex Differences In Circulating Bdnfmentioning
confidence: 99%
“…To assess if such AIS plasticity actually occur in schizophrenia, we used postnatal MK-801 (an NMDA receptor antagonist) model. Transient exposure to MK-801 during the neonatal period causes behavioral changes in rodents such as hyperlocomotion, stereotyped behavior, sensorimotor gating, and cognitive deficits representing schizophrenia-like symptoms (Feinstein & Kritzer, 2013;Furuie, Yamada, & Ichitani, 2013;Nozari, Shabani, Hadadi, & Atapour, 2014, Nozari, Mansouri, Shabani, Nozari, & Atapour, 2015Nozari, Shabani, Farhangi, Mazhari, & Atapour, 2015;Zhou, Chen, Hu, Mao, & Kong, 2013). Underlying these behavioral changes are a decrease in the function of different neurotransmitter systems such as glutamatergic, dopaminergic, and GABAergic system (Abekawa, Ito, Nakagawa, & Koyama, 2007;Hoftman & Lewis, 2011;Jones, Corbin, & Huntsman, 2014;Weinstein et al, 2016).…”
mentioning
confidence: 99%
“…However, a "three-hit" model of selective breeding after subchronic ketamine administration and post-weaning social isolation, showed female specific enhanced PPI impairments, but more pronounced working and reference memory deficits in males (Kekesi et al 2015 (Cui et al 2015). In a study that specifically focused on the sex differences in this drug-induced rat model, it was found that females were more affected by MK-801 in tests of ataxia, locomotion and stationary behaviour, while males displayed more stereotype thigmotaxis but reduced rearing and grooming (Feinstein et al 2013). This increased locomotor and ataxia response to MK-801 in females was previously reported by Andine et al, who found that females show locomotor and ataxia behavioural responses to MK-801 at much lower doses (0.2mg/kg) than males (effect only found at 1mg/kg) and furthermore, females displayed ~ 25 times higher serum and brain levels of MK-801 than male rats administered the same dose, suggesting sex-specific metabolising mechanisms may underlie these behavioural differences (Andine et al 1999).…”
Section: Drug-induced Modelsmentioning
confidence: 99%